Age- and Sex-Related Variations in Platelet Count Among Healthy Tharu in Banke, Nepal - Ghimire, Pragya Gautam; Ghimire, Prasanna; Prasad Rauniyar, Abhishek; Chaurasiya, Namrata (Nepal Journal of Medical Sciences, 2026)
Introduction: Standard platelet reference ranges derived from Western populations often misclassify physiological variations in Nepal’s indigenous Tharu ethnicity, who exhibit unique genetic adaptations including high hemoglobinopathy prevalence. The objective of this study is to establish age and sex specific platelet count reference intervals among hemoglobinopathy negative healthy Tharu individuals attending a tertiary hospital in Banke district. Methods: Hospital-based cross-sectional study (January-June 2025) enrolled 240 Tharu individuals (≥5 years) via systematic sampling from hemoglobinopathy screening programs, routine health check-ups, and pre-employment fitness certificates at Nepalgunj Medical College Teaching Hospital (NGMCTH). Participants required normal hemoglobin electrophoresis (HbA2 ≤3.5%). Platelet counts used Sysmex XN-1000 analyzer with manual verification of outliers. Data stratified by age (5-14, 15-64, ≥65 years) and sex; 2.5th-97.5th percentiles defined intervals. Statistical analysis: ANOVA, t-tests, Pearson correlation (SPSS v26; p<0.05). Results: Overall mean platelet count was 218.4 ± 85.2 ×10⁹/L with reference interval 58.0-453.0 ×10⁹/L. Females showed higher counts (221.5 ± 86.1 ×10⁹/L) than males (212.7 ± 83.4 ×10⁹/L), though not statistically significant (p = 0.264). Significant age-related decline observed (r = -0.28, p = 0.002), with highest median in 5-14 years group (168.8 ×10⁹/L), followed by 15-64 years (205.0 ×10⁹/L), and ≥65 years (165.0 ×10⁹/L). ANOVA confirmed significant differences among age groups (F = 3.21, p = 0.043). Conclusions: Tharu-specific intervals reveal lower medians with pronounced age-related decline and female predominance. Hospital-derived reference ranges from hemoglobinopathy-screened individuals will improve diagnostic accuracy and reduce misclassification in clinical practice